THE INFLUENCE OF RESTAURANT ATTRIBUTES ON MUSLIM CONSUMERS TOWARDS SUBSCRIBING HALAL RESTAURANT IN COMPARISON STUDY: BOGOR AND KOTA KINABALU - Andika Nuraga Budiman; Hilma Suyana (Jurnal Manajemen Pemasaran, 2021)
Halal certification does not only mean not only the food served halal but also the entire process must be halal as well. Therefore, Halal certification is important in the aspect of Indonesian and Malaysian food industry especially in the Halal Restaurant. This study objective is to understand the influence of Restaurant’s attribute Restaurant and extrinsic on consumer’s attitude and subscribing of the Halal Restaurant from Malaysian and Indonesian consumers. In addition, this study expecting the result comparison between Bogor and Kota Kinabalu respondent. This study used 200 respondents in total; each city received half of the targeted number of respondents. This study used quantitative method to reach respondents; they are Muslims who wanted to consume Halal food and beverages. The result shows that, among Muslims, we found the different perception towards subscribing Halal Restaurant , we considered that Bogor respondents only give attention in Restaurant service quality attributes when they are subscribing Halal Restaurant Meanwhile, this study found that Kota Kinabalu respondents are very consider about quality, value, and risk. The point of this result is even they are same religion; they still have different perspective and perception.